Pathological significance and therapeutic prospects of HCCS expression patterns in lung adenocarcinoma - Pengfei Luo; Sixuan Wu; Zhimin Li; Shuangfeng Tan; Lijun Zeng; Yuanbing Tang; Lunqi Luo; Yuehua Li; Zhaohui Tang (Cell Adhesion & Migration)
This study examines Holocytochrome c synthase (HCCS) expression in lung adenocarcinoma (LUAD) and its impact on the tumor immune environment. By analyzing multiple tumor databases, the research highlights HCCS expression patterns across various cancer types, focusing on its correlation with M2-type macrophages, which aid tumor progression. Findings show that high HCCS expressionin LUAD is associated with increased M2-type macrophages, and variations in HCCS levels influence immune cell infiltration and cancer therapy responsiveness. It suggests that HCCS significantly shapes the immune landscape within tumors, promoting growth and spread, and underscores its potential as a therapeutic target in LUAD and other cancers with similar expression profiles.